Influence of motor imagery training on hip abductor muscle strength and bilateral transfer effect - Alenezi, Majid Manawer; Hayes, Amy; Lawrence, Gavin P.; Kubis, Hans-Peter (Frontiers in Physiology, 2023)
Motor imagery training could be an important treatment of reduced muscle function in patients and injured athletes. In this study, we investigated the efficacy of imagery training on maximal force production in a larger muscle group (hip abductors) and potential bilateral transfer effects. Healthy participants (n=77) took part in two experimental studies using two imagery protocols ( 30 min/day, 5 days/week for 2 weeks) compared either with no practice (study 1), or with isometric exercise training (study 2). Maximal hip abduction isometric torque, electromyography amplitudes (trained and untrained limbs), handgrip strength, right shoulder abduction (strength and electromyography), and imagery capability were measured before and after the intervention. Post intervention, motor imagery groups of both studies exhibited significant increase in hip abductors strength ( 8%, trained side) and improved imagery capability. Further results showed that imagery training induced bilateral transfer effects on muscle strength and electromyography amplitude of hip abductors. Motor imagery training was effective in creating functional improvements in limb muscles of trained and untrained sides.